2013
DOI: 10.1002/cbin.10079
|View full text |Cite
|
Sign up to set email alerts
|

Functional impact of cholesterol sequestration on actin cytoskeleton in normal and transformed fibroblasts

Abstract: Membrane cholesterol and lipid rafts are implicated in various signalling processes involving actin rearrangement in living cells. However, functional link between raft integrity and organisation of cytoskeleton remains unclear. We have compared the effect of cholesterol sequestration on F-actin structures in normal and transformed fibroblasts in which microfilament system is developed to a different extent. The depletion of membrane cholesterol by methyl-beta-cyclodextrin (MbCD) resulted in a disruption of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Recent reports that cholesterol depletion perturbs cytoskeletal organization (Ramprasad et al, 2007; Sun et al, 2007; Qi et al, 2009; Norman et al, 2010; Chubinskiy-Nadezhdin et al, 2013; Dick et al, 2013) may suggest that cholesterol depletion inhibits antigen patching by preventing the cytoskeletal proteins from actively clustering the crosslinked antigens. But, as mentioned above, if the cytoskeleton, and not lipid rafts, mediates the clustering of crosslinked antigens, the finding that crosslinking induces glycosphingolipid capping implies the glycosphingolipids in the outer leaflet of the plasma membrane are indirectly associated with cytoskeletal proteins.…”
Section: Glycosphingolipid Redistribution Induced By Antigen Crosslinmentioning
confidence: 99%
“…Recent reports that cholesterol depletion perturbs cytoskeletal organization (Ramprasad et al, 2007; Sun et al, 2007; Qi et al, 2009; Norman et al, 2010; Chubinskiy-Nadezhdin et al, 2013; Dick et al, 2013) may suggest that cholesterol depletion inhibits antigen patching by preventing the cytoskeletal proteins from actively clustering the crosslinked antigens. But, as mentioned above, if the cytoskeleton, and not lipid rafts, mediates the clustering of crosslinked antigens, the finding that crosslinking induces glycosphingolipid capping implies the glycosphingolipids in the outer leaflet of the plasma membrane are indirectly associated with cytoskeletal proteins.…”
Section: Glycosphingolipid Redistribution Induced By Antigen Crosslinmentioning
confidence: 99%
“…Interestingly, recent in vivo experiments have shown that actin filaments that are attached to the membrane induce the formation of liquid-ordered domains1415. Conversely, cholesterol sequestration alters the ratio between liquid-ordered (raft-like) and liquid-disordered lipid phases, causing dramatic changes in the dynamics of the actin cytoskeleton16. All this evidence suggests a dynamic interplay between the actin cytoskeleton and the lipid membrane that alters the normal diffusion of proteins in the membrane17.…”
mentioning
confidence: 99%
“…Therefore membrane CHO and not SM was critical for TSH-TSHR interaction. Depletion of membrane CHO by methyl-beta-cyclodextrin resulted in a disruption of lipid rafts in plasma membrane [26] whereas extensive sphingolipid depletion did not affect lipid raft integrity [27]. Rapid changes of the cytoskeleton as reaction to gravitational changes were reported in diverse cell types [28], [29] and they could be responsible for changes in surface receptors [1].…”
Section: Discussionmentioning
confidence: 99%